Development of a simple mechanical model to evaluate running economy for designing running augmentation suits - Hiromu Mori; Takayuki Tanaka; Akihiko Murai; Takashi Kusaka; Yumeko Imamura (ROBOMECH Journal)
Abstract This paper presents a simple mechanical model capable of evaluating a running effectiveness index $$ε _{EI}$$ ϵ EI based on mechanical energy. We extended a spring-loaded inverted pendulum model, considering the biomechanical determinants of running economy (RE), to develop a simplified mechanical model that can accurately represent the $$ε _{EI}$$ ϵ EI calculated by a detailed running model. To assess the accuracy of the proposed model in estimating RE, we computed the $$ε _{EI}$$ ϵ EI using both the proposed and detailed models, based on data obtained from running experiments. A linear regression analysis using the least squares method was performed to analyze the relationship between the $$ε _{EI}$$ ϵ EI values calculated by the two models. The regression analysis results of the $$ε _{EI}$$ ϵ EI values obtained from the two models yielded significant F-statistics ( $$p < 0.01$$ p < 0.01 ) for all four participants, demonstrating that the proposed model can sufficiently represent the running economy index calculated by the detailed model.